Coupled dynamic response of a three-column mini TLP (Journal of Naval Architecture and Marine Engineering, 2010)
For the development of deepwater marginal fields, many new platform concepts and designs are on the anvil. The mini TLP is a proven concept in this regard wherein an optimised conventional TLP system economically and efficiently serves in developing small marginal deepwater reserves. Various new geometric configurations and designs of mini TLPs are reported in the literature. This paper presents a new geometric configuration which could be a better alternative to an existing configuration. A 3-column mini TLP is designed and its platform-mooring coupled dynamic behaviour is investigated and compared with an existing 4-column mini TLP. The numerical investigation is carried out for the 1:56 scaled model using a finite element computer program suitable for compliant offshore platforms. A combination wave force model with diffraction-radiation loading on large members and Morison loading on slender members is adopted for computing the non-linear dynamic response of the structure. The effects of parameters such as pretension in tethers and wave approach angle have been studied. The results obtained are compared with published results of the 4-column mini TLP. It is found that the dynamic responses of the 3-column mini TLP are close to the 4-column mini TLP with relatively higher surge and tether tension.  Accounting for this in the design stage, the newly designed structure could be a promising candidate which can be used as an alternative to the 4-column mini TLP. Reducing the number of columns from four to three has added advantages in terms of cost and time during fabrication, installation and maintenance of the platform. Keywords: Deepwater structures; Coupled dynamics; Finite element method; Mini TLP; Nonlinear dynamicanalysis. DOI: 10.3329/jname.v6i2.2789